Інформаційно-вимірювальна система оцінки змінного періоду (MCIT: Proceedings of International scientific and practical conference, 2025)
The work estimates the variable frequency and variable period of a person's heartbeat after physical exertion. Examples of obtaining the specified grades are considered. The obtained results open promising directions for further research of real signals with a variable period, in particular, electrocardiograms obtained during or after the effect on the organism of excitation.
Keywords: periodic functions with variable period, variable period heartbeat, heart rate, approximation of variable period, heart rate variability, arrhythmia estimation